2020
DOI: 10.47391/jpma.897
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of diabetic retinopathy among diabetic patients

Abstract: Objectives: To assess the awareness of diabetic patients about diabetic retinopathy. Method: The cross-sectional study was conducted at the Ophthalmology Department, Fauji Foundation Hospital, Rawalpindi, Pakistan, from April 2018 to April 2019, and comprised diabetic patients of either gender aged 21-80 years. A pre-tested semi-structured questionnaire was used to collect data on socio-demographic, diabetes and diabetic retinopathy characteristics. Fundoscopic examination was done, and the presence and stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“… 5 The prevalence of DR in Pakistan was estimated to be 28.78% in all diabetics but observed with inconsistent frequency of DR and PDR. 6 Rizwan et al, reported low awareness and outcomes of diabetic retinopathy in diabetics in Pakistan 7 Early detection, strict vigilance of blood glucose, blood pressure, and lipids may decrease the risk of developing DR. Dyslipidemia in Diabetes Type-I and II is strongly associated with the onset and progression of DR Dyslipidemia plays role in early events of DR development 8 but the link between peripheral lipids and retinal microvascular pathology in T2DM is still not clear. In view of this, the present study aims to investigate the role of serum lipids in the onset and progression of Diabetic Retinopathy in Type-II diabetic individuals.…”
Section: Introductionmentioning
confidence: 99%
“… 5 The prevalence of DR in Pakistan was estimated to be 28.78% in all diabetics but observed with inconsistent frequency of DR and PDR. 6 Rizwan et al, reported low awareness and outcomes of diabetic retinopathy in diabetics in Pakistan 7 Early detection, strict vigilance of blood glucose, blood pressure, and lipids may decrease the risk of developing DR. Dyslipidemia in Diabetes Type-I and II is strongly associated with the onset and progression of DR Dyslipidemia plays role in early events of DR development 8 but the link between peripheral lipids and retinal microvascular pathology in T2DM is still not clear. In view of this, the present study aims to investigate the role of serum lipids in the onset and progression of Diabetic Retinopathy in Type-II diabetic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that 51% of all the patients with blindness due to DR come from the Asia-Pacific region. The prevalence of DR among patients with DM ranges from 10% in India to 43% in Indonesia within the Asia-Pacific ( 43 , 44 ). The highest number of people with DM is in China (116 million), which reflects the rapid economic growth and urbanization in China with significant lifestyle and dietary changes ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Daha önce farklı bir popülasyonda DRP farkındalığını inceleyen bir çalışmada hastaların yarısından fazlasının diyabetin gözleri etkileyebileceğinin farkında olmasına rağmen, DRP ve sonuçları açısından farkındalıklarının düşük olduğu görülmüştür. 24 Bu durum DRP'nin kronik bir süreç olması ve hastalardaki semptomların genelde aniden olmayıp yavaş yavaş gelişmesi, bu nedenle hastalarda DRP farkındalığının oluşmaması ile ilgili olabilir.…”
Section: Discussionunclassified